Growing up Muslim in Europe and the United States - Bozorgmehr, Medhi; Kasinitz, Philip; Bozorgmehr, Mehdi (Studies in migration and diaspora, 2018)
"This volume brings together scholarship from two different, and until now, largely separate literatures--the study of the children of immigrants and the study of Muslim minority communities--in order to explore the changing nature of ethnic identity, religious practice, and citizenship in the contemporary western world. With attention to the similarities and differences between the European and American experiences of growing up Muslim, the contributing authors ask what it means for young people to be both Muslim and American or European, how they reconcile these, at times, conflicting identities, how they reconcile the religious and gendered cultural norms of their immigrant families with the more liberal ideals of the western societies that they live in, and how they deal with these issues through mobilization and political incorporation. A transatlantic research effort that brings together work from the tradition in diaspora studies with research on the second generation, to examine social, cultural, and political dimensions of the second-generation Muslim experience in Europe and the United States, this book will appeal to scholars across the social sciences with interests in migration, diaspora, race and ethnicity, religion and integration"--